The Relationship between of Some Pathogens and Gallstones Formation - Maytham Abas Makki (Journal of Global Pharma Technology, 2018)
The study was conducted from October 2016 to February 2017 at Al Hussein Educational Hospital in Samawah city. Forty-five patients diagnosed with gallstones which removed by surgical operation the gallbladder,then the bacterial implantation of all the isolated grits from the residual gallbladder.Most of the factors related to diseases of the infected were also recorded. Forty-five percent of the men and women aged 2-43 , 20 - 54 yearsrecpectivly .Three types of gravel were identified depending on appearance, size and color. Cholesterol stone (15.55%), pigmentedstone  (33.33 %) and mixed stone (51.11%).The results showed that all of these species were positive for bacterial culture and recorded species:Enterococcus faecales (88.88%), Klebsiella pneumonia (22.22%), Enterobacteraerogenes (28.88 %), Pseudomonas aerugenosa (77.7%) Vibrio alginolyticus (20%),Vibrio valunificus (46.6%), Escherichia coli (55.55%),Vibrio parahemolyticus (15.55%),،( Proteus merabilis (66.6%) Listeria monocytogenes (60 %   ( Staphylococcus aureus (42.22%), Staphylococcus epidermidis (4.44 %), Staphylococcus saprophyticus (6.66%), Proteus vulgaris (2.22%) ,Citrobacterfreundii (51.55%),Salmonella typhi (37.77 %), Salmonella entritidis 13.33% , Coliform bacteria (15.55 %).Keywords: Pathogens;  Gallstones formation; Enterococcus faecales.